Hydrophobicity and outer membrane proteins of Shigella dysenteriae type 1 after treatment with subinhibitory concentrations of aminoglycosides - Hostacká, A; Karelová, E (Folia microbiologica, 1997)
Hydrophobicity and profiles of outer membrane proteins of Shigella dysenteriae type 1 after treatment with subinhibitory concentrations (1/2 or 1/4 of the MIC) of aminoglycosides were studied. The antimicrobial activity of the antibiotics tested was 3.12 mg/L (amikacin, tobramycin) and 6.25 mg/L (gentamicin). The hydrophobicity of the cell surface of S. dysenteriae type 1 was decreased after exposure to all aminoglycosides at a concentration of 1/2 of the MICs; 1/4 of the MICs of the antibiotics did not affect bacterial aggregation in the presence of ammonium sulfate. SDS-polyacrylamide gel electrophoresis showed that the profiles of outer membrane proteins of the strain treated with aminoglycosides at both subinhibitory concentrations were not changed as compared to the control.
Keywords: elektroforéza v polyakrylamidovém gelu; Bacterial Outer Membrane Proteins; Chemical Phenomena; Anti-Bacterial Agents; gentamiciny; proteiny vnější bakteriální membrány; Chemistry, Physical; fyzikální chemie; tobramycin; chemické jevy; buněčná stěna; Electrophoresis, Polyacrylamide Gel; Amikacin; Tobramycin; amikacin; Gentamicins; Shigella dysenteriae; antibakteriální látky; Cell Wall